Between hope and reality: Challenges of islamic education teachers in implementing the independent curriculum at muhammadiyah 5 junior high school surakarta - Muhammad Alfan Wiandani; Isfihani; Iffah Mukhlisah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to comprehensively describe the implementation of the